Field evaluation of levo 2.4 sl (Botanical) for the Management of Insect Pests of Eggplant (Solanum melongena L.) and Okra (Abelmoschus esculentus L. Moench) - Nyaaba Aetiba, John Peter (2015)
A Thesis Submitted to the Department of Crop and Soil Sciences, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana In Partial Fulfillment of the Requirement for the Degree Of Masters of Philosophy in Crop Protection (Entomology).